Beyond science : the wider human context - Polkinghorne, J. C. (Cambridge University Press, 1996)
John Polkinghorne has had a distinguished career as a particle physicist and as an author of books exploring themes in science and religion. In Beyond Science Polkinghorne examines the nature of scientific inquiry itself and the human context in which science operates. The book looks to issues of meaning and value, such as scientific competition and subjectivity, as well as more practical aspects of the discipline as the conference circuit and the nurturing of new research. Throughout, Polkinghorne offers an accessible and personal view of science and its relationship to the human spirit.